Estudio de factibilidad para la creación de una microempresa productora y comercializadora de tilapia roja en el barrio la Trinidad de la parroquia Malacatos, cantón Loja - Sócola Escobar, Byron (2014)
There is a global trend towards intensification of aquaculture-based systems, however a large portion of word production from aquaculture is still in small-scale “rural type” and extensive systems. The term “rural aquaculture” has been used to distinguish, from other production systems, the culture of aquatic organisms by families through extensive or semi-intensive systems, for home consumption or partial marketing. Studies conducted in varius regions of Ecuador suggested that rural aquaculture of tilapia could be an alternative activity, able to dampen the demand and reduce pressure on natural resources. This paper analyzes the culture of tilapia considering the minimum management, with low fish density and low water exchange with the intention to suggest simple techniques of production that could be implemented in poor rural peri-urban areas of tropical Ecuador. For the development of this research, 6 specific variables that are detailed below arises:  Market research: in the La Trinidad there is only one producer of tilapia, which offer the same 45.45 kg a year, while consumer demand for tilapia over 3 504,5 kg.  Study of the technical management of the production of tilapia.  Economic Survey of tilapia production.  Financial evaluation of tilapia production.  Analysis of the environmental impact generated by the project in the neighborhood La Trinidad.  Análisis de la sensibilidad económica del proyecto.  Analysis of the economic sensitivity of the project The methodology is structured around the establishment of a diagnostic process for reality focused on the supply and demand of tilapia in the La Trinidad parish Malacatos Canton Loja, with the data collected it was determined that the aforementioned population has great response to the meat of tilapia, but not consumed regularly due to lack of production in the sector. Diagnostic process after an economic study in which it was determined that tilapia production generates a significant margin, able to cover the basic needs required by entrepreneurial performance is developed. The results are:  The offer is 3485.07 kg of tilapia, using a stepped output per year which covers much of the lawsuit filed in the sector.  The project reaches a NPV of 13,357,80  There is a product of the production of tilapia a benefit cost 1.32, meaning that for every dollar earned 32 cents earned.  Implementation of the project will generate positive impacts on both the social context (creating jobs) and environmental (conservation of natural resources).  The TIR of this project is 21,28%, allowing us to make an investment loan of up to 21,28%%.  The balance point of this project is 63,94%.